Prevenindo desordens músculo esqueléticas: avaliação postural do acadêmico de odontologia - Bizelli, Guilherme Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Postural assessment in dental students can be considered as an excellent detection strategy for the prevention of musculoskeletal changes. We conducted a cross-sectional study with students enrolled in a university, which should have attended at least one clinical discipline that contemplated in his teaching plan (n = 303). The objective of this study was to evaluate the posture of dental students and pinpoint the location of their amendments. For evaluation of body posture used the Portland State University protocol - PSU, based on observation instrument to check symmetry, asymmetry and possible deviations and / or postural changes between the body segments and regions. The evaluator quantifies the percentage (%) and the Postural Correction Index (PCI) of the evaluated through mathematical equations that are stipulated by the diagnostic score, ie, total and by regions. are adopted as evaluation criteria three scales: 5 - without deviation, 3 - slight lateral deviation and 1 - sharp lateral deviation. At the end of data collection were analyzed 142 students with a mean age of 22 years. Regarding the ICP found an average of 98.04%. When analyzed the means of each body segment, regions of head and neck (CPR) and dorsal and lumbar spine (RCDL) achieved the best rates (97.38% and 98.69). But to individually analyze each student, values were found below considered good (≥ 80%). In the evaluation of body posture, on average, these students showed values above the stipulated as good for this methodology. With this, it points out the need for body awareness and adoption of ergonomic measures to maintain these levels in order to avoid future postural changes, which may result in numerous injuries and decreased working capacity

A avaliação postural em alunos de odontologia pode ser considerada como uma excelente estratégia de detecção para a prevenção de alterações músculo esquelética. Realizou-se um estudo transversal com alunos regularmente matriculados em uma universidade, os quais deveriam ter cursado ao menos uma disciplina clínica que contemplasse em seu plano de ensino (n=303). Objetivou-se com esse estudo avaliar a postura corporal de alunos de odontologia e apontar a localização das respectivas alterações. Para avaliação da postura corporal utilizou-se o protocolo da Portland State University - PSU, instrumento pautado na observação para verificar simetrias, assimetrias e possíveis desvios e/ou alterações posturais entre os segmentos corporais e regiões. O avaliador quantifica o percentual (%) e o Índice de Correção Postural (ICP) do avaliado por meio das equações matemáticas que são estipuladas pelo escore diagnóstico, ou seja, o total e por regiões. Adotam-se como critério de avaliação três escalas: 5 - sem desvio, 3 - ligeiro desvio lateral e 1 - acentuado desvio lateral. Ao final da coleta dos dados foram analisados 142 alunos, com idade média de 22 anos. Em relação ao ICP encontrou-se uma média de 98,04%. Quando analisadas as médias de cada segmento corpóreo, as regiões de cabeça e pescoço (RCP) e coluna dorsal e lombar (RCDL) obtiveram os melhores índices (97,38% e 98,69). Porém ao analisar individualmente cada aluno, foram encontrados valores abaixo do considerado como bom (≥ 80%). Na avaliação da postura corporal, em média, estes acadêmicos apresentaram valores acima do estipulado como bom para essa metodologia. Com isto, cabe ressaltar a necessidade de consciência corporal e adoção de medidas ergonômicas para manutenção destes índices, a fim de se evitar alterações posturais futuras, que poderão acarretar em inúmeras lesões e diminuição da capacidade de trabalho
Keywords: Estudantes de odontologia; Dor musculoesquelética; Engenharia humana; Students, Dental